An Analysis of the Crisis of Essentialism in Islamic Religious Education in the Digital Era - Muttakin, Khaerul; Nisa’, Azzyra Sholikhatun; Uyun, Aulia Qurratil (Indo-MathEdu Intellectuals Journal, 2026)
The digital era has brought significant transformation to Islamic Religious Education (PAI), resulting in a crisis of essentialism in which the core values of Islamic teachings—such as tawhid, morality, and worship—are increasingly reduced to symbolic expressions rather than deeply internalised spirituality. This study aims to analyse the crisis of essentialism in PAI and explore strategies for revitalising its essential meaning amid the dominance of digital culture. Using a qualitative library research method, data were collected from books, journal articles, and scientific publications relevant to Islamic education and digital culture. The findings show that digital media has fostered a form of superficial religiosity characterised by performative piety, weak moral reflection, and diminished transcendental awareness. This crisis is mainly caused by the dominance of visual-symbolic culture, low levels of religious digital literacy, limited pedagogical adaptation among PAI teachers, and an unresponsive curriculum to contemporary challenges. To address these issues, the study proposes integrative and transformative strategies, including strengthening religious digital literacy, applying reflective-contextual pedagogy, implementing project-based learning, and redefining the teacher’s role as a spiritual mentor. Strengthening a school culture rooted in Islamic spirituality is also crucial to restoring the depth and authenticity of Islamic values.